The Role of Artificial Intelligence in Shaping Economic Analysis and Finance: An In-Depth Study - Gupta, Dr. Ashish; Gupta, Dr. DV; Arya, Swati; Renu (Metallurgical and Materials Engineering, 2025)
Artificial Intelligence (AI) is revolutionizing the way economies are analyzed and financial decisions are made. This paper delves into the profound impact of AI on economic analysis and finance, exploring its transformative potential and the challenges it presents. By examining the integration of AI technologies in economic modeling, financial forecasting, risk assessment, and decision-making processes, the study highlights the evolving landscape of economic and financial analysis. Through a comprehensive review of existing literature and real-world applications, the paper aims to provide insights into how AI is reshaping traditional methodologies and fostering innovation in the field. The findings underscore the need for adaptive regulatory frameworks, interdisciplinary collaboration, and continuous learning to harness the full benefits of AI in economic and financial contexts. 24